Recognizing object surface materials to adapt robotic disinfection in infrastructure facilities. (10th January 2022) - Hu, Da; Li, Shuai
Abstract: Existing disinfection robots are not intelligent enough to adapt their actions to object surface materials for precise and effective disinfection. To address this problem, a new framework is developed to enable the robot to recognize various object surface materials and to adapt its disinfection methods to be compatible with recognized object surface materials. Specifically, a new deep learning network is proposed that integrates multi‐level and multi‐scale features to classify the materials on contaminated surfaces requiring disinfection. The infection risk of contaminated surfaces is computed to choose the appropriate disinfection modes and parameters. The developed material recognition method demonstrates state‐of‐the‐art performance, achieving an accuracy of 92.24% and 91.84% on the Materials in Context Database validation and test datasets, respectively. The proposed method was also tested and evaluated in the context of healthcare facilities, where the material classification achieved an accuracy of 89.09%, and the adaptive robotic disinfection was successfully implemented.